Perancangan Desain Pola Parkir Sepeda Motor Menggunakan Metode Ergonomi Partisipatori (Studi Kasus : Universitas PGRI Wiranegara) - Aditya Perdana Putra, Andika Rangga; Surya Putra Kencana, Artha Aulia (Industrika : Jurnal Ilmiah Teknik Industri, 2024)
The limited access to public transportation to Universitas PGRI Wiranegara (UNIWARA) has increased the preference for using private vehicles, thereby emphasizing the need for adequate parking facilities. This study aims to create an optimal design for motorcycle parking patterns at UNIWARA that aligns with user needs, utilizing the Participatory Ergonomics method. Through three participatory ergonomic stages, namely the initial interview stage, group discussion stage, and parking pattern design stage, several issues were identified, including the irregular use of parking facilities, suboptimal capacity, poor vehicle circulation, and excessive interventions by parking attendants. The result of the motorcycle parking design using participatory ergonomics revealed a total capacity of 732 motorcycles in three parking sectors. The design specifications include a parking angle of 90°, a parking unit width of 0.75 meters, a parking unit length of 2 meters, and a parking circulation lane width exceeding 1.5 meters. These specifications address the identified issues and provide a well-structured parking environment that meets the needs and comfort of users. Keywords: Participatory Ergonomics, Parking Facilities, Parking Pattern